A sweeping change in borehole seismic sources - Dean, Timothy; Puckett, M.; Lane, D.; Tulett, J.; McClay, M. (2013)
Copyright © (2012) by the European Association of Geoscientists & Engineers All rights reserved.Vibrators are the preferred sources for onshore vertical seismic profile (VSP) surveys. Truck-mounted units are especially useful as they are more road mobile than buggy-based units. In particular, they can be driven directly to the wellsite, resulting in improved response times, simplified logistics with fewer vehicles and personnel at the wellsite and improved transport safety. Acquiring broad-bandwidth, high-quality VSP data, using state-of-the art vibrator equipment, however, has generally required the use of the latest buggy-mounted vibrators, compromising well-site logistics and transportation safety for VSP operations. To deliver optimum performance, two new truck vibrator models specifically designed to take advantage of all of the most recent developments in vibrator technology while retaining the logistical advantages of truck-mounted units have been developed. These new truck-mounted vibrators offer greatly improved data quality with tests showing that they can transmit a signal with a frequency bandwidth of 6.6 octaves compared to previous models which can only transmit 2.5 octaves. Being mounted on modern truck chassis these vehicles retain all the mobility and HSE advantages of truck vibrators.